2012
DOI: 10.1007/s10067-012-1975-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of TNF-α and Fas gene promoter polymorphism with the risk of Kashin–Beck disease in Northwest Chinese population

Abstract: The objective of this study is to investigate the relationship between single-nucleotide polymorphisms (SNPs) of the tumor necrosis factor-α (TNF-α) and Fas genes and Kashin-Beck disease (KBD) in Shaanxi province, Northwest in China. Blood samples of 388 residents were collected from 14 KBD villages in Linyou and Yongshou counties, Shaanxi, Northern of China. One hundred eighty-six cases with KBD and 202 cases of health in KBD areas were diagnosed by "Diagnosis Criterion of Kashin-Beck disease in China (WS/T20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The clinical manifestations and pathologic changes of KBD are generally similar to that of osteoarthritis (OA) [5], suggesting the common genetic mechanism shared by KBD and OA. This hypothesis is supported by previous genetic studies, which identified common susceptibility genes for KBD and OA, such as TNF and HLA-DRB1 [6][7][8][9][10]. Multiple GWAS of OA have been conducted by now.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…The clinical manifestations and pathologic changes of KBD are generally similar to that of osteoarthritis (OA) [5], suggesting the common genetic mechanism shared by KBD and OA. This hypothesis is supported by previous genetic studies, which identified common susceptibility genes for KBD and OA, such as TNF and HLA-DRB1 [6][7][8][9][10]. Multiple GWAS of OA have been conducted by now.…”
Section: Introductionsupporting
confidence: 56%
“…In rabbit knees, interleukin-1 (IL1) and tumor necrosis factor (TNF) could enhance the expression of substance P and accelerate cartilage degradation [19]. It is interesting that IL1 and TNF have been found to involve in the articular cartilage damage of KBD [6,20,21]. Given the roles of TACR1 in the functional maintenance of articular cartilage and pathogenesis of arthritis, it is reasonable to infer that TACR1 contributed to the joint damage of KBD.…”
Section: Discussionmentioning
confidence: 97%
“…Various causes have been suggested, including: selenium (Se) deficiency alone or in combination with iodine deficiency [78]; ingesting of grains with mycotoxins [4]; and excess of fulvic acid, but none of the proposed explanations is entirely satisfactory [9]. In recent years, more attention has been paid to potential genetic etiologies of KBD [1012]. The Yongshou KBD study was designed to assess potential genetic etiologies of KBD.…”
Section: Introductionmentioning
confidence: 99%